Upaya Cultural Framing Suara Rakyat Malaysia Untuk Mendapat Dukungan Bagi The Abolish ISA Movement - Linda Juwita, Ni Putu Gian; Juwita, Ni Putu Gian Linda; Resen, Putu Titah Kawitri (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2017)
The Internal Security Act (ISA), is said as one of  law that violate fundamental rights of Malaysian peopla. The government used this law to against their political enemies with detention without trial rule. In response to this, Suara Rakyat Malaysia (SUARAM) form The Abolish ISA Movement. Trough  The Abolish ISA Movement, Suara Rakyat Malaysia consistently require the Government of Malaysia to repeal ISA. Even tough this movement become succeed to be the biggest movement in Malaysia’s history, can not make The Abolish ISA Movement free from any obstacle. This movement is restricted by the Government of Malaysia, the restriction including repressive action, such as arresting and detaining the activist of The Abolish ISA Movement. To maintain the existence of The Abolish ISA Movement, SUARAM initiate to gathering support from transnational actors through cultural framing and the formation of transnational advocacy network. Keyword: The Abolish ISA Movement, Cultural Framing, Transnational Advocacy Network